Efeito da suplementação de vitamina D nas exacerbações pulmonares da fibrose cística : um ensaio clínico randomizado crossover - Ongaratto, Renata (2021)
Background: Pulmonary exacerbations are associated with a worse evolution of cystic fibrosis (CF) and their control is of great importance in the treatment of disease. Extra skeletal properties of vitamin D have been pointed out, but the effect of its supplementation on markers of CF-related pulmonary disease is unclear. Methods: A randomized crossover trial conducted at a CF center in southern Brazil was used to evaluate the effect of an extra-dose supplementation regimen of vitamin D (5,000 IU/day <5 years and 10,000 IU/day ≥5 years) on pulmonary exacerbations in CF patients. Subjects were randomly allocated to receive vitamin D followed by standard treatment, or standard treatment followed by vitamin D for three months. Each treatment period was separated by a 9-month washout. The primary outcome was the number of pulmonary exacerbations during the intervention period. Additionally, a period of six months after the use of the extra dose of vitamin D was evaluated. The change in serum concentration of 25(OH)D after the end of supplementation was evaluated as a secondary outcome. Results: Thirty-four patients participated in the study (median age 5.16 years). Sixteen patients received vitamin D first, and 18 received standard treatment first. There was a borderline statistical difference (p=0.10) in pulmonary exacerbations during the use of the extra dose of vitamin D. No effect of vitamin D on pulmonary exacerbations was observed in a period of six months after the end of supplementation. More than half of the patients had suboptimal levels of 25(OH)D pre-supplementation, and only 58% achieved desirable vitamin levels. Conclusion: Our findings indicate a possible effect of vitamin D in reducing CF pulmonary exacerbations and reinforce the high prevalence of hypovitaminosis D in these patients, despite routine vitamin supplementation. Large studies, multicenter studies and/or metanalyses are necessary. Brazilian Clinical Trials Registry (ReBEC): RBR-439vzm